The effect of arterial hypertension on thrombosis in low‐risk polycythemia vera - Tiziano Barbui; Alessandro M. Vannucchi; Alessandra Carobbio; Elisa Rumi; Guido Finazzi; Heinz Gisslinger; Marco Ruggeri; Maria Luigia Randi; Mario Cazzola; Alessandro Rambaldi; Bettina Gisslinger; Lisa Pieri; et al. (2016)
To the Editor: With the intent to avoid potentially unnecessary exposure to chemotherapy, cyto-reductive drugs are currently recommended only in high-risk patients with polycythemia vera (PV).However, the prevention of venous and arterial vascular complications still represents an unmet clinical need both in low and high risk PV patients. An annual rate of thrombosis around 2% in low risk and greater than 3% in high risk cases was documented in recent studies 1. These figures exceed the estimates in control, matched population without a myeloproliferative neoplasm (MPN) where the annual rates of arterial and venous thrombosis are around 0.5% and 0.1% respectively 2. Thus, one might argue whether, in the presence of such residual risk of thrombosis in conventionally defined low risk PV patients, treatment with phlebotomy and aspirin only as currently recommended, may not be fully appropriate. Furthermore, the possibility exists that different subgroups of low risk PV patients might be identified suggesting the opportunity of different personalized treatment. Theoretical support to this reasoning derives from recent studies in ET where conventionally assigned low risk patients were sub-categorized in different risk classes based on the presence of JAK2 mutation and cardiovascular risk factors; these two variables accounted for a 2.6% annual rate of major thrombotic events compared to 0.44% in patients without the aforementioned risk factors 3. Thus, in subgroups of "low" risk PV, conventionally treated with phlebotomy and aspirin, one could argue for the rationale of investigating the value of presumably non-leukemogenic drugs, such as interferon-alpha. Accordingly, in the present study we critically analyzed multiple variables predicting thrombosis in an inception multicenter cohort of 604 strictly WHO-defined PV patients conventionally considered at low-risk of thrombosis. The aim was to recognized subgroups at different incidence of thrombosis in which to propose more appropriate treatments. After approval from their respective institutional review boards, seven centers from Italy, Vienna (Austria) and Mayo Clinic in Rochester (US) belonging to the International Working Group for myeloproliferative neoplasm (MPN) Research and Treatment (IWG-MRT), collectively submitted diagnostic and follow-up information on 604 patients categorized into low-risk group. Objectively proven major arterial and venous events were considered. Arterial hypertensionmwas defined at PV diagnosis in patients who were receiving anti-hypertension drugs. Time to thrombosis was determined from the time of diagnosis to the time of the first episode of thrombosis or last follow-up, censoring patients when they became older than 60 years during the follow-up. Kaplan–Meier product-limit method was used and the log-rank test was adopted to compare survival curves. Receiver operating characteristic (ROC) analysis was used to select the best cut-off of continuous variables in terms of their sensitivity and specificity. The characteristics of the cohort (Supporting Information Table 1) reflect well the heterogeneity of epidemiologic and clinical features that are found in the routine clinical practice of low-risk PV patients. All patients were treated with aspirin and phlebotomy to keep hematocrit (HCT) target <45%. Cytoreductive therapy (hydroxyurea in the great majority) was initially needed in 8% of patients due to extreme leukocytosis and thrombocytosis and/or splenomegaly. After a median of 4.9 years (range: 0–34), 75 patients (12%) experienced 84 major thrombotic events including venous (45%) and arterial occlusions (55%). By ROC analysis we selected two age groups at different rates of incident thrombosis and in univariate analysis age 50–60 years and arterial hypertension were associated with significant higher rate of arterial events. In contrast, these two factors were not significantly associated with venous events. In multivariate model, only arterial hypertension retained the statistical difference while a non-significant trend for thrombosis was found for patients with age 50–60 years (P = 0.09). By Kaplan-Meier analysis, a significant different thrombosis-free survival (P = 0.025) was documented in the two groups (Fig. 1). In patients without hypertension (66%), the thrombosis free survival was double in comparison with the group with hypertension (34%); the difference was evident after 4 years of diagnosis. Arterial thrombosis-free survival in low-risk PV patients according to hypertension. Legend: HTN= Hypertension; IR=Incidence Rate; CI=Confidence Interval To examine whether increased HCT was associated with a higher incidence of hypertension, we divided our patients in two groups at different HCT levels. By ROC analysis, the best cut-off to discriminate patients with or without hypertension was 58%. The comparison between the frequency of hypertension in the highest HCT group (39%) versus the lowest group (xx%) was significantly different (P = 0.043). The current study demonstrates that, among the cardiovascular risk factors (active smoking, diabetes, hypercholesterolemia), arterial hypertension had the most relevant prognostic role for the incidence of arterial thrombosis in patients conventionally defined at low risk for future vascular complications. This may be, at least in part, related to the well documented relationship between increased hematocrit level and arterial hypertension 4. In support of this, we found that its frequency in PV cases was higher than in a series of 891 patients with ET (Odds Ratio = 1.38, P = 0.022), adjusted for age and sex, indicating that in these patients hypertension is strictly associated with the increased HCT levels. Further evidence of this association is the demonstration that the frequency of hypertension was associated with the highest baseline HCT levels. Therefore, these findings underscore the notion that enhanced blood viscosity may lead to increased peripheral resistance to blood flow and, consequently, to an enhanced frequency of arterial hypertension. A potential limitation of our study is its retrospective design; however, the strength is the large sample size, the well-defined patient population, the evaluation of patients at diagnosis, and the long follow-up period. Based on these results, two points of practical importance deserve to be addressed. The first is that overall, these findings suggest to revise the conventional criteria for risk stratification of patients with low-risk PV by including further stratification based on presence of hypertension. Such distinction is practically relevant arising the question whether the current recommendation to treat low-risk cases with phlebotomy plus aspirin is still adequate or rather a more intensive therapeutic approach, also including non leukemogenic cyto-reductive drugs such as alpha-Interferon, might be necessary. This suggestion may apply particularly in low-risk patients with age 50-60 in whom multivariate analysis showed an independent trend for the incidence of arterial thrombosis. The second point to be considered in this context regards the choice of antihypertensive. Recent studies have shown that in the bone marrow of PV patients, the renin-angiotensin system (RAS) is overexpressed and leads, in addition to hypertension, to bone marrow hematopoietic progenitor cell stimulation 5. Moreover, there are observations that angiotensin-converting-enzyme (ACE) inhibitors reduce packed cell volume and hemoglobin concentration in polycythemia that follows renal transplantation 6. Results of a randomized clinical trial in patients with altitude polycythemia indicated that long-term treatment with low doses of enalapril safely prevented increase in arterial blood pressure and progressively reduced packed cell volume and hemoglobin concentration 7. Therefore, ACE inhibitors could represent the most effective therapy in PV patients to control arterial hypertension and perhaps the excessive cell production. In conclusion, low-risk PV patients with arterial hypertension represent a subgroup in which a more intensive therapy should be explored in prospective studies designed to examine whether the addition of cytoreductive drugs to phlebotomy and aspirin and ACE inhibitors may reduce the still high incidence of thrombosis. This work was done under the auspices of the AGIMM (AIRC-Gruppo Italiano Malattie Mieloproliferative) project. A detailed description of the AGIMM project is available at http://www.progettoagimm.it Tiziano Barbui,1* Alessandro M. Vannucchi,2 Alessandra Carobbio,1 Elisa Rumi,3 Guido Finazzi,4 Heinz Gisslinger,5 Marco Ruggeri,6 Maria Luigia Randi,7 Mario Cazzola,3 Alessandro Rambaldi,4 Bettina Gisslinger,5 Lisa Pieri,2 Juergen Thiele,8 Animesh Pardanani,9 and Ayalew Tefferi9 1FROM Research Foundation, Papa Giovanni XXIII hospital, Bergamo, Italy; 2Department of Experimental and Clinical Medicine, University of Florence, Florence, Italy; 3Department of Hematology, University of Pavia, IRCCS Policlinico San Matteo, Pavia, Italy; 4Division of Hematology, Papa Giovanni XXIII hospital, Bergamo, Italy; 5Division of Hematology, Medical University of Vienna, Vienna, Austria; 6Division of Hematology, S. Bortolo Hospital, Vicenza, Italy; 7Department of Hematology, University of Padua, Padua, Italy; 8Institute of Pathology University of Cologne, Cologne, Germany; 9Division of Hematology Department of Medicine, Mayo Clinic, Rochester, Minnesota Additional Supporting Information may be found in the online version of this article. Supporting Information Please note: The publisher is not responsible for the content or functionality of any supporting information supplied by the authors. Any queries (other than missing content) should be directed to the corresponding author for the article.